Arthur and the invisibles 2 & 3 : [videorecording (DVD)] the new minimoy adventures - Besson, Luc; Highmore, Freddie, 1992-; Miller, Logan; Farrow, Mia, 1945- (Twentieth Century Fox Home Entertainment, 2011)
Arthur 2 : The revenge of Maltazard: Arthur travels back to the Minimoy world and joins forces with his old friend Max and the feisty Princess Selenia only to discover the evil Maltazard is up to his old tricks!